Educação em sociedades complexas: desafios para ressignificar sociopedagógica e politicamente a escola - Marcon, Telmo; Piaia , Consuelo Cristine (Linhas Críticas, 2014)
This bibliographic paper proposes to reflect on education in the context of complex societies, placed within the reframing of the school. The text begins by problematizing complex societies, to then question the limits of the science model that has become hegemonic and analyze two pedagogical traditions that have deeply influenced formal education: the traditional and the modern. Lastly, we will refer to the itinerant school of MST, as an education experience that allows for overcoming the school-and-society dichotomy, which also brings new elements to reframe the school in face of the challenges set by complex societies.